Evaluation of the efficacy of vacuum cleaners for the integrated control of brown spider Loxosceles intermedia - Ramires,E. N. (2007)
Some venomous spiders of the genus Loxosceles can reach high population densities inside and around houses. In Brazil, most spider accidents are related to Loxosceles intermedia. Control of loxoscelism should utilize integrated pest management tools, such as vacuum cleaners, to eliminate egg sacs, webs and spiders. The present study tested the efficacy of one type of vacuum cleaner (for professional and domestic use) in the control of L. intermedia populations. Cockroaches (Pycnoscelus surinamensis) were used in some tests for comparison. Vacuuming using standard accessories or a paper tube resulted in the death of all female (n=60), male (n=60), young (n=60) and just-hatched (n=60) L. intermedia, and all egg sacs (n=5) were destroyed. The removal of the plastic plate present at the bottom of the vacuuming tube inside the machine allowed some spiders to survive the vacuuming process. When kept inside a vacuum bag full of dust and debris, adult females (n=10) survived for 10 days; however, significant mortality was observed among male (n=10) and young individuals (n=10). Addition of cornstarch to the vacuum bag did not affect the spiders (n=20). Vacuum cleaners, such as the one used in the present investigation, are promising tools for integrated management of L. intermedia and other spiders in domestic environments.